Laboratory friction measurements of Nankai Trough basalts - Matt J Ikari; Frederike Kristina Wilckens; Demian M Saffer (PANGAEA, 2020)
We obtained altered basaltic upper basement from the modern Nankai Trough seaward of the trench, recovered by drilling on IODP Expedition 333. We performed laboratory friction experiments on bare surfaces and gouge powders of this material, in addition to and in combination with other materials for comparison. Based our friction data, we suggest that in addition to creep the altered Nankai basalts may also allow the possibility of slow slip events.